2012
DOI: 10.1074/jbc.m111.275057
|View full text |Cite
|
Sign up to set email alerts
|

Unique Peptide Substrate Binding Properties of 110-kDa Heat-shock Protein (Hsp110) Determine Its Distinct Chaperone Activity

Abstract: Background: Hsp110, an Hsp70 homolog, is highly efficient in preventing protein aggregation but lacks the folding activity seen in Hsp70s. Results: In contrast to Hsp70s, Hsp110s exhibit distinct peptide substrate binding properties. Conclusion:The peptide substrate binding properties determine the chaperone activity differences between Hsp70s and Hsp110s. Significance: Our studies shed light on the molecular mechanism of the chaperone activities of Hsp70s and Hsp110s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
118
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 66 publications
14
118
0
1
Order By: Relevance
“…The intrinsic peptide substratebinding activity is represented by the peptide substratebinding affinity in the presence of ADP. Consistent with published results (Kumar et al 2011;Xu et al 2012), the binding affinity for this F-NR peptide for WT DnaK was around 1.69 μM in the presence of ADP (Fig. 3b, c).…”
Section: Resultssupporting
confidence: 91%
“…The intrinsic peptide substratebinding activity is represented by the peptide substratebinding affinity in the presence of ADP. Consistent with published results (Kumar et al 2011;Xu et al 2012), the binding affinity for this F-NR peptide for WT DnaK was around 1.69 μM in the presence of ADP (Fig. 3b, c).…”
Section: Resultssupporting
confidence: 91%
“…An allosteric communication between the NBD and the substrate-binding domain of Hsp110 has been recently reported (54). Our dose responses further showed that, as suggested from the crystal structure of yeast Hsp110 with bovine Hcp70 NBD, equimolar Hsp70 and Hsp110 can optimally refold stable aggregated luciferase, likely by binding to orthologous topological sites in their respective NBDs and by effective reciprocal allosteric signals of similar quality and intensities between the two orthologous SBDs (42).…”
Section: Discussionsupporting
confidence: 75%
“…Like Hsp70s, Hsp110 can hydrolyze ATP (33) and is activated by J-domain co-chaperones (34). Hsp110 can also bind nascent polypeptide chains (33,34,53) and small peptides with different specificities (54). By doing so, Hsp110 may act as a "holding" chaperone that passively prevents the aggregation of stress-or mutation-induced misfolding and aggregating proteins (55).…”
Section: Discussionmentioning
confidence: 99%
“…To monitor long-range changes upon perturbation of L 34 , we performed CSP analysis on a previously characterized DnaK construct deficient for peptide binding (9). For this construct, called DnaK-L 34 , the entire L 34 (TAEDNQS) was replaced by a shorter sequence (MGG) from a DnaK homologous protein, Hsp110 (9,27). In the domain-undocked conformation, this construct has low substrate affinity-similar to domain-docked (ATP-bound) WT DnaK (27).…”
Section: Resultsmentioning
confidence: 99%